Catching COBRAs - Muntinga, Daan, ....- (Amsterdam : SWOCC, 2013)
With social media usage increasingly widespread and influential, companies face the challenge of inspiring and cultivating Consumers' Online Brand-Related Activities (COBRAs). This dissertation argues that they can do effectively only when they have a good understanding of consumers' willingness to engage with brands on social media. Academic research on this matter, however, is scarce. Instead of adding to the already substantial body of effect-oriented studies, this research therefore considers more deeply the question of what determines and motivates COBRA. In doing so, it provides practical insights into how to inspire consumer's engagement with brands on social media and fills an important hiatus in the academic literature on marketing, branding, and consumer behaviior.
Keywords: Consumentengedrag; Sociale media